Insights on catheter-related bloodstream infections: a prospective observational study on the catheter colonization and multidrug resistance. (May 2022) - Pinto, M.; Borges, V.; Nascimento, M.; Martins, F.; Pessanha, M.A.; Faria, I.; Rodrigues, J.; Matias, R.; Gomes, J.P.; Jordao, L.
Summary: Background: Central venous catheter-related bloodstream infection (CRBSI) is a huge public health concern with considerable impact on mortality and health costs. Aim: A three-year observational study enrolling three tertiary hospitals located in Lisbon, Portugal, was designed to identify the major aetiological agents of CRBSI, their ability to colonize central venous catheters and their antimicrobial resistance profiles. Methods: Aetiological agents of CRBSI were identified by Vitek 2. Whole-genome sequencing was used to confirm CRBSI by the most prevalent aetiological agents and characterize their resistome. Central venous catheter colonization (namely by biofilm assembly) was monitored by scanning electron microscopy. Findings: Staphylococci were the most prevalent causative agent (36/58, 62.0%), with S. aureus and coagulase-negative S. epidermidis accounting for 24.1% and 36.2% of CRBSIs, respectively. Fifty-nine of 72 staphylococci isolates were meticillin resistant. Comparative genomic analysis of central venous catheters/haemoculture pairs of isolates revealed genomic matches for 35 of 36 pairs and a good correlation between antibiotic susceptibility phenotype and the presence of antimicrobial resistance genetic determinants. Biofilms were present on 48.6% of the central venous catheters; nevertheless, no statistically significant association was established between biofilm assembly and CRBSI, and the presence/absence of ica operon and agr groups did not correlate with biofilm phenotypes, highlighting the need for further studies to elucidate biofilms' role on this healthcare-associated infection. Conclusion: Whole-genome sequencing was shown to be a valuable tool to confirm CRBSI. Although more than 42.3% of the central venous catheters were colonized by staphylococci, no statistically significant association was found between CRBSI and biofilms.